Manipulating Cellular Interactions of Poly(glycidyl methacrylate) Nanoparticles Using Mixed Polymer Brushes - Clemons, T.; Challenor, M.; Fitzgerald, Melinda; Dunlop, S.; Smith, N.; Swaminathan Iyer, K. (2016)
There is a growing need for the development of nanoparticles, with imaging and drug delivery capabilities, to maintain cellular uptake but avoid protein attachment and recognition. In this study we have demonstrated that nanoparticles consisting of a poly(glycidyl methacrylate) (PGMA) core and a mixed brush architecture of methoxypoly(ethylene glycol) and poly(ethylenimine) (mPEG–PEI) on the surface can meet this need. Surface functionalization with PEI alone results in cellular uptake, but rapid protein attachment whereas PEG alone can avoid protein attachment but to the detriment of cellular uptake. A mixed copolymer brush of both PEI and mPEG provides the ideal balance.